Effects of Drinking-Water Filtration on Cryptosporidium Seroepidemiology, Scotland - Colin N. Ramsay; Adam P. Wagner; Chris Robertson; Huw V. Smith; Kevin G.J. Pollock (Emerging Infectious Diseases, 2014)
Continuous exposure to low levels of Cryptosporidium oocysts is associated with production of protective antibodies. We investigated prevalence of antibodies against the 27-kDa Cryptosporidium oocyst antigen among blood donors in 2 areas of Scotland supplied by drinking water from different sources with different filtration standards: Glasgow (not filtered) and Dundee (filtered). During 2006–2009, seroprevalence and risk factor data were collected; this period includes 2007, when enhanced filtration was introduced to the Glasgow supply. A serologic response to the 27-kDa antigen was found for ≈75% of donors in the 2 cohorts combined. Mixed regression modeling indicated a 32% step-change reduction in seroprevalence of antibodies against Cryptosporidium among persons in the Glasgow area, which was associated with introduction of enhanced filtration treatment. Removal of Cryptosporidium oocysts from water reduces the risk for waterborne exposure, sporadic infections, and outbreaks. Paradoxically, however, oocyst removal might lower immunity and increase the risk for infection from other sources.